Coated diaphragm and preparation method thereof
By applying a covalent triazine frame on the lithium battery separator, the problems of poor wetting and low liquid retention rate of the separator to the electrolyte are solved, and higher liquid absorption and liquid retention capacity and longer cycle life are achieved, which enhances the Comprehensive performance and safety of lithium batteries.
Patent Information
- Application Number
- CN202310952385.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium battery separators have poor wetting properties on the electrolyte, low liquid retention rate and excessive pores, resulting in serious growth of lithium dendrites, reducing the safety and application restrictions of lithium batteries.
Using a covalent triazine frame as the component of the coating layer, the thermal stability, liquid absorption and liquid retention capacity of the diaphragm is improved through the stability, strong polarity and nano-scale pore structure of the covalent triazine frame, and the anion migration is inhibited. , reduce the internal polarization of the battery.
It improves the comprehensive performance of lithium batteries, including higher liquid absorption and liquid retention capabilities, longer cycle life and higher capacity, while reducing internal polarization of the battery and enhancing safety.
Smart Images

Figure CN119447696A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular, to a coated diaphragm and a preparation method thereof. Background Art
[0002] Lithium batteries are widely used as effective devices for energy conversion and storage. Diaphragms are one of the key materials for lithium batteries. The pores of the diaphragm provide channels for the migration of lithium ions during the charge and discharge process of the battery, and isolate the positive and negative electrodes to avoid internal short circuits in the battery. The liquid absorption and liquid retention capabilities of the diaphragm directly affect the capacity and cycle life of the battery. However, most polyolefin diaphragms currently used have disadvantages such as poor wettability to electrolytes and low liquid retention rates. Moreover, for lithium metal batteries, the pores of polyolefin diaphragms are too large, concentration polarization is obvious, and lithium dendrite growth is more serious, which reduces the safety of lithium batteries and limits their application. Solutions to the above problems include developing new diaphragms and coating the diaphragm surface.
[0003] Surface coating of the diaphragm is a common solution. At present, the surface coating of the diaphragm mainly includes two methods: one is to coat the surface of the diaphragm with inorganic materials to enhance the mechanical properties and puncture resistance of the diaphragm, improve the heat resistance, and thus improve the high temperature safety and cycle performance of the battery. However, the high mass density of inorganic materials will reduce the overall energy density of the battery. At the same time, the coated inorganic materials will reduce the porosity of the diaphragm surface, which is not conducive to the diffusion of lithium ions; the second is to coat the surface of the polyolefin diaphragm with polymer materials to improve the battery's liquid retention rate and long-term cycle performance, but the overall performance of the battery is not good. At the same time, the polymer coating is immersed in the electrolyte for a long time, and it is easy to swell and fall off; in addition, the coating will increase the thickness of the diaphragm, thereby increasing the ohmic resistance inside the battery. Summary of the invention
[0004] The purpose of the present application is to provide a coated diaphragm and a preparation method and application thereof, which can improve the comprehensive performance of the battery.
[0005] In a first aspect, an embodiment of the present application provides a coated diaphragm, the coated diaphragm comprising: a base film and a coating layer; the coating layer is attached to at least a portion of the base film, and the coating layer comprises a covalent triazine framework.
[0006] In the above implementation process, by using the covalent triazine framework as a component of the coating layer, the covalent triazine framework is a type of porous organic polymer with good stability, ordered structure, strong polarity, large specific surface area and controllable pore size. Its good stability can improve the thermal stability of the coated diaphragm; the smaller mass density will not have a significant effect on the battery energy density; the high specific surface area and strong polarity can increase the affinity of the diaphragm to the electrolyte, so that the diaphragm has higher liquid absorption and retention capabilities; the nanoscale pore structure can inhibit anion migration, reduce the internal polarization of the battery, and increase the capacity and cycle life of the battery, thereby achieving the effect of improving the overall performance of the battery.
[0007] As an optional embodiment, the covalent triazine framework includes a plurality of interconnected microporous units, and the structural formula of the microporous unit is: Among them, R includes at least one of a benzene ring, biphenyl, pyridine, naphthalene and anthracene; ○ includes at least one of a triazine structure and a triphenylamine structure, and at least one ○ is a triazine structure. To a certain extent, the size of the R group will positively affect the pore size of the covalent triazine framework, and the size of the pore size of the covalent triazine framework will affect the migration of lithium ions and anions. R is selected from a benzene ring, biphenyl, pyridine, naphthalene and anthracene, and the pore size of the triazine framework can be controlled to a suitable size, which can inhibit the migration of anions and accelerate the migration of lithium ions, thereby reducing the internal polarization of the battery and effectively improving the capacity and cycle life of the battery. At the same time, the number of triazine structures in ○ positively affects the nitrogen content of the covalent triazine framework to a certain extent. The higher the nitrogen content of the covalent triazine framework, the greater the polarity, and then after being assembled into a battery, its affinity with the electrolyte is better. The covalent triazine framework is composed of multiple microporous units of the same structure, which can effectively improve the uniformity of the performance of the coated diaphragm. After being assembled into a battery, the current distribution can be uniform during the charge and discharge process to avoid polarization.
[0008] As an optional embodiment, the covalent triazine framework comprises:
[0009]
[0010]
[0011]
[0012] At least one of .
[0013] As an optional embodiment, the mass of the covalent triazine framework is 50%-90% of the mass of the coating layer; or the mass of the covalent triazine framework is 70%-90% of the mass of the coating layer. To a certain extent, the mass proportion of the covalent triazine framework in the entire coating layer is positively correlated with the improvement of the comprehensive performance of the coated diaphragm. The greater the mass proportion of the covalent triazine framework in the entire coating layer, the better the improvement of the comprehensive performance of the coated diaphragm.
[0014] As an optional embodiment, the coating layer has an adhesion amount of 0.01-0.1 mg / cm 2 ; or the coating layer adhesion on the base film is 0.01-0.05mg / cm 2 The amount of coating layer attached to the base film is positively correlated to the thickness of the coating layer to a certain extent. The smaller the thickness of the coating layer, the lower its cost. At the same time, it can reduce the porosity of the coating layer, making the migration path of lithium ions in a shorter range, reducing the impact on their migration. At the same time, the amount of coating layer attached to the base film also affects the uniformity of the coating layer to a certain extent. The better the uniformity of the coating layer, the more uniform the current distribution during the charge and discharge process after being assembled into a battery, avoiding polarization.
[0015] As an optional embodiment, the coating layer has a thickness of 0.1-2 μm; the coating layer has a thickness of 0.21-2 μm; or the coating layer has a thickness of 0.3-1 μm; or the coating layer has a thickness of 0.3-0.8 μm. The thickness will affect the length of the migration path of lithium ions. Generally, the smaller the thickness of the coating layer, the less the porosity of the coating layer can be reduced, so that the migration path of lithium ions is in a shorter range, reducing the impact on their migration; at the same time, the smaller the thickness, the smaller the consumption of the coating slurry, which effectively saves the preparation cost of the coated diaphragm.
[0016] As an optional embodiment, the size of the covalent triazine framework is 0.1-2 μm; or the size of the covalent triazine framework is 0.1-1.0 μm; or the size of the covalent triazine framework is 0.2-0.8 μm. It is understood that if the size of the covalent triazine framework is too large, pore blocking may occur, thereby affecting the porosity of the diaphragm and the performance of the battery diaphragm.
[0017] As an optional embodiment, the coating layer is attached to at least a portion of one side of the base film, or the coating layer is attached to at least a portion of both sides of the base film.
[0018] As an optional embodiment, the coating layer further comprises a binder, and the binder comprises an oily binder or an aqueous binder; optionally, the oily binder comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer and polyimide, and the aqueous binder comprises at least one of polyacrylic acid binder, polyurethane binder, polyacrylonitrile binder, polyacrylate binder, carboxymethyl cellulose lithium binder, carboxylated chitosan binder, styrene-butadiene emulsion and polytetrafluoroethylene emulsion; and / or
[0019] The coating layer also includes a functional material, which includes a ceramic nanomaterial or a two-dimensional flaky inorganic material; optionally, the ceramic nanomaterial includes at least one of aluminum oxide, silicon nitride, titanium nitride, aluminum nitride, zirconium diboride, zirconium nitride and molybdenum nitride, and the two-dimensional flaky inorganic material includes at least one of boron nitride, carbon nitride, molybdenum disulfide, molybdenum antimonide, tungsten disulfide, calcium sulfide and titanium selenide; and / or
[0020] The base film is a polyolefin diaphragm; optionally, the polyolefin diaphragm is a polypropylene diaphragm, a polyethylene diaphragm, or a polypropylene / polyethylene / polypropylene three-layer composite diaphragm.
[0021] In a second aspect, an embodiment of the present application provides a method for preparing a coated diaphragm, the method comprising: mixing components of a coating layer with a solvent, wherein the components of the coating layer include a covalent triazine framework, to obtain a coating slurry; applying the coating slurry to a base film, and then removing the solvent to obtain a coated diaphragm.
[0022] The coated diaphragm prepared by this method has good thermal stability and higher affinity for electrolyte, and thus has higher liquid absorption and retention capabilities; at the same time, it can inhibit anion migration, reduce internal polarization of the battery, and increase the capacity and cycle life of the battery, thereby achieving the effect of improving the overall performance of the battery.
[0023] As an optional embodiment, the mass proportion of the covalent triazine framework in the coating slurry is 1%-20%; or the mass proportion of the covalent triazine framework in the coating slurry is 1%-10%; or the mass proportion of the covalent triazine framework in the coating slurry is 1%-5%, and the mass proportion of the covalent triazine framework in the coating slurry is 3%-5%. The smaller the mass proportion of the covalent triazine framework in the coating slurry, the more uniform its dispersion in the slurry, which provides a basis for the preparation of a thinner coating layer. At the same time, it can make the covalent triazine framework more evenly distributed on the surface of the base film. After being assembled into a battery, the current distribution during the charge and discharge process can be uniform, avoiding polarization.
[0024] As an optional embodiment, the components of the coating layer are mixed with a solvent, wherein the components of the coating layer include a covalent triazine framework to obtain a coating slurry, including:
[0025] Dispersing the covalent triazine framework in the coating layer in a solvent to obtain a first dispersion;
[0026] dispersing the remaining components of the coating layer in a solvent to obtain a second dispersion;
[0027] The first dispersion liquid and the second dispersion liquid are mixed to obtain a coating slurry.
[0028] In the above implementation process, mixing the components separately is more conducive to the dispersion of the covalent triazine framework, and the uniformity of the dispersion of the covalent triazine framework will affect the uniformity of the coating layer. Generally, the more uniform the covalent triazine framework is dispersed, the better the coating uniformity of the coating slurry on the base film. After it is applied and assembled into a battery, the current distribution during the charge and discharge process can be uniform, avoiding polarization.
[0029] In a third aspect, an embodiment of the present application provides a lithium battery, wherein the lithium battery comprises the coated diaphragm provided in the first aspect or the coated diaphragm prepared by the method for preparing the coated diaphragm provided in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0032] Figure 1 This is a SEM image of the coating layer provided in Example 1 of the present application;
[0033] Figure 2 A constant rate charge and discharge curve diagram of a battery assembled with the coated diaphragm provided in Example 1 of the present application and a diaphragm purchased from the market at 1C;
[0034] Figure 3 This is a graph of ionic conductivity obtained by AC impedance spectroscopy of a battery assembled from a coated diaphragm provided in Example 1 of the present application;
[0035] Figure 4 Optical test results of the contact angle of the electrolyte of the coated diaphragm provided in Example 1 of the present application Figure 1 ;
[0036] Figure 5 Optical test results of the contact angle of the electrolyte of the coated diaphragm provided in Example 1 of the present application Figure 2 ;
[0037] Figure 6 Optical test results of the electrolyte contact angle of commercially available separators Figure 1 ;
[0038] Figure 7 Optical test results of the electrolyte contact angle of commercially available separators Figure 2 ;
[0039] Figure 8 A flowchart of a method provided in an embodiment of the present application. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0042] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0043] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0044] An embodiment of the present application provides a coated diaphragm, which includes: a base film and a coating layer; the coating layer is attached to at least a portion of the base film, and the coating layer includes a covalent triazine framework.
[0045] The base membrane generally has pores, which provide channels for the migration of lithium ions during the charge and discharge process of the battery. At the same time, the base membrane serves to isolate the positive and negative electrodes and avoid internal short circuits in the battery. Usually, the base membrane can be a polyolefin separator; illustratively, the polyolefin separator can be selected from a polypropylene separator, a polyethylene separator, and a polypropylene / polyethylene / polypropylene three-layer composite separator.
[0046] The coating layer is a functional layer attached to the base film, which can improve the problems of poor wettability of the base film to the electrolyte and low liquid retention rate. Usually, in addition to the active ingredient (the active ingredient in this application is the triazine framework), the coating layer may also contain a binder and other additives, which mainly play the role of better dispersing and adhering the active ingredient to the base film. The binder can be an oily binder or an aqueous binder. Exemplarily, the oily binder can be selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer and polyimide; the aqueous binder can be selected from at least one of polyacrylic acid binders, polyurethane binders, polyacrylonitrile binders, polyacrylate binders, carboxymethyl cellulose lithium binders, carboxylated chitosan binders, styrene-butadiene emulsions and polytetrafluoroethylene emulsions.
[0047] The covalent triazine framework refers to a polymer containing a triazine structure, which has the advantages of good stability, ordered structure, rich nitrogen content, large specific surface area and controllable pore size. In this embodiment, the crystal form of the covalent triazine framework can be amorphous, semi-crystalline or highly crystalline.
[0048] The coating layer being attached to at least a portion of the base film means that the coating layer is attached to a portion of or the entire surface of the base film. At the same time, the coating layer may be attached to only one side of the base film, or to both sides of the base film at the same time.
[0049] The above design uses a covalent triazine framework as a component of the coating layer. The covalent triazine framework is a type of porous organic polymer with good stability, ordered structure, strong polarity, large specific surface area, and controllable pore size. Its good stability can improve the thermal stability of the coated diaphragm; the smaller mass density will not have a significant effect on the battery energy density; the high specific surface area and strong polarity can increase the affinity of the diaphragm to the electrolyte, so that the diaphragm has higher liquid absorption and retention capabilities; the nanoscale pore structure can inhibit anion migration, reduce the internal polarization of the battery, and increase the capacity and cycle life of the battery, thereby achieving the effect of improving the comprehensive performance of the battery.
[0050] In some embodiments, the covalent triazine framework has the structural formula: Wherein, R includes at least one of a benzene ring, biphenyl, pyridine, naphthalene and anthracene. It should be noted that R at each point can be independently selected from a benzene ring, biphenyl, pyridine, naphthalene and anthracene, and R at each point can be the same or different; ○ includes at least one of a triazine structure and a triphenylamine structure, and at least one ○ is a triazine structure, and the structural formula of the triazine structure is: To a certain extent, the size of the R group will positively affect the pore size of the covalent triazine framework, and the size of the pore size of the covalent triazine framework will affect the migration of lithium ions and anions. R is selected from benzene ring, biphenyl, pyridine, naphthalene and anthracene, which can control the pore size of the triazine framework to a suitable size, inhibit the migration of anions, and accelerate the migration of lithium ions, thereby reducing the internal polarization of the battery and effectively improving the capacity and cycle life of the battery. At the same time, the number of triazine structures in ○ positively affects the nitrogen content of the covalent triazine framework to a certain extent. The higher the nitrogen content of the covalent triazine framework, the greater the polarity, and then after being assembled into a battery, its affinity with the electrolyte is better.
[0051] In some embodiments, the covalent triazine framework comprises a plurality of interconnected microporous units, the structural formula of the microporous unit being: Wherein, R includes at least one of a benzene ring, biphenyl, pyridine, naphthalene and anthracene. It should be noted that R can be independently selected from a benzene ring, biphenyl, pyridine, naphthalene and anthracene, and R at each point can be the same or different; ○ includes at least one of a triazine structure and a triphenylamine structure, and at least one ○ is a triazine structure. In each microporous unit, the number of triazine structures can be 1-6. For example, the number of triazine structures is 1, 2, 3, 4, 5 and 6, and the structural formula of the triazine structure is: The covalent triazine framework is composed of multiple microporous units with the same structure, which can effectively improve the uniformity of the performance of the coated diaphragm. After being assembled into a battery, it can make the current distribution uniform during the charging and discharging process and avoid polarization.
[0052] Exemplarily, the covalent triazine framework can be
[0053]
[0054] wait.
[0055] In some embodiments, the size of the covalent triazine framework may be 0.1-2 μm; further, the size of the covalent triazine framework may be 0.1-1.0 μm; further, the size of the covalent triazine framework may be 0.2-0.8 μm.
[0056] The size of the covalent triazine framework is determined by measuring the particle size of the composite particles of the covalent triazine framework in a solution state using a dynamic light scattering instrument (DLS), that is, the hydrated particle size (hydrodynamic diameter).
[0057] Exemplarily, the size of the covalent triazine framework can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm and 2μm, etc., and it can also be any other value in the range of 0.1-2μm.
[0058] In some embodiments, the mass of the covalent triazine framework may be 50%-90% of the mass of the coating layer; further, the mass of the covalent triazine framework may be 70%-90% of the mass of the coating layer.
[0059] The covalent triazine framework mass being 50% to 90% of the mass of the coating layer means that a value obtained by dividing the value of the covalent triazine framework mass by the value of the mass of the coating layer is 50% to 90%.
[0060] Exemplarily, the mass of the covalent triazine framework may be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc. of the mass of the coating layer, or any other value within the range of 50%-90%.
[0061] To a certain extent, the mass proportion of the covalent triazine framework in the entire coating layer is positively correlated with the improvement in the comprehensive performance of the coated diaphragm. The greater the mass proportion of the covalent triazine framework in the entire coating layer, the better the improvement in the comprehensive performance of the coated diaphragm.
[0062] In some embodiments, the coating layer may have an attachment amount of 0.01-0.1 mg / cm 2 Furthermore, the coating layer may have an adhesion amount of 0.01-0.05 mg / cm 2 .
[0063] The adhesion amount refers to the mass of the coating layer attached to the base film per unit area.
[0064] For example, the coating layer may be deposited on the base film in an amount of 0.01 mg / cm 2 , 0.014mg / cm 2 , 0.02mg / cm 2 , 0.03mg / cm 2 , 0.04mg / cm 2 , 0.05mg / cm 2 , 0.054mg / cm 2 , 0.06mg / cm 2 , 0.07mg / cm 2 , 0.08mg / cm 2 , 0.09mg / cm 2 and 0.1mg / cm 2 etc., which can also be 0.01-0.1 mg / cm 2 Any other value in the range or a range of values between any two values.
[0065] The amount of coating layer attached to the base film is positively correlated to the thickness of the coating layer to a certain extent. The smaller the thickness of the coating layer, the lower its cost. At the same time, it can reduce the porosity of the coating layer, making the migration path of lithium ions in a shorter range, reducing the impact on their migration. At the same time, the amount of coating layer attached to the base film also affects the uniformity of the coating layer to a certain extent. The better the uniformity of the coating layer, the more uniform the current distribution during the charge and discharge process can be after assembling into a battery, avoiding polarization.
[0066] In some embodiments, the coating layer has a thickness of 0.1-2 μm; or the coating layer has a thickness of 0.21-2 μm; or the coating layer has a thickness of 0.3-1 μm; or the coating layer has a thickness of 0.3-0.8 μm.
[0067] Exemplarily, the thickness of the coating layer can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm and 2μm, etc., and it can also be any other value in the range of ≤2μm.
[0068] The thickness will affect the length of the migration path of lithium ions. Generally speaking, the smaller the thickness of the coating layer, the less likely it is that the porosity of the coating layer will decrease, making the migration path of lithium ions shorter and reducing the impact on their migration. At the same time, the smaller the thickness, the smaller the loss of the coating layer, which effectively saves the preparation cost of the coated diaphragm.
[0069] In some embodiments, the coating layer may further include functional materials to improve the performance of the coated diaphragm. The functional materials may be ceramic nanomaterials or two-dimensional flaky inorganic materials. For example, the ceramic nanomaterials may be selected from at least one of aluminum oxide, silicon nitride, titanium nitride, aluminum nitride, zirconium diboride, zirconium nitride and molybdenum nitride. The two-dimensional flaky inorganic materials may be selected from at least one of boron nitride, carbon nitride, molybdenum disulfide, molybdenum antimonide, tungsten disulfide, calcium sulfide and titanium selenide. The above materials have the advantages of good heat resistance and high chemical stability, can enhance the mechanical properties and puncture resistance of the coated diaphragm, improve heat resistance, and thus improve the high temperature safety and cycle performance of the battery.
[0070] The coating thickness and covalent triazine framework content of the coated diaphragm can be adjusted according to different needs; and the preparation method of the coated diaphragm is simple, without the need to develop a new base film, and only requires coating on the surface of an existing commercial diaphragm. It is easy to operate, environmentally friendly, and easy to carry out large-scale industrial production and application.
[0071] The coated diaphragm is introduced above, and its preparation method is described in detail below.
[0072] The embodiment of the present application provides a method for preparing a coated diaphragm, the method comprising: mixing the components of the coating layer with a solvent, the components of the coating layer comprising a covalent triazine framework, to obtain a coating slurry; applying the coating slurry to a base film, and then removing the solvent to obtain a coated diaphragm. The coated diaphragm prepared by this method has good thermal stability; high electrolyte affinity, and thus has higher liquid absorption and liquid retention capabilities; at the same time, it can inhibit anion migration, reduce internal polarization of the battery, and increase the capacity and cycle life of the battery; thereby achieving the effect of improving the overall performance of the battery.
[0073] Specifically, the methods include:
[0074] S1. The components of the coating layer are mixed with a solvent, wherein the components of the coating layer include a covalent triazine framework to obtain a coating slurry;
[0075] In some embodiments, the mass proportion of the covalent triazine framework in the coating slurry can be 1%-20%; further, the mass proportion of the covalent triazine framework in the coating slurry can be 1%-10%; or the mass proportion of the covalent triazine framework in the coating slurry can be 1%-5%, or the mass proportion of the covalent triazine framework in the coating slurry is 3%-5%.
[0076] The mass proportion of the covalent triazine framework in the coating slurry being 1% to 20% means that the mass of the covalent triazine framework is divided by the mass of the coating slurry to obtain a result value of 1% to 20%.
[0077] Exemplarily, the mass proportion of the covalent triazine framework in the coating slurry can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% and 20%, etc., and it can also be any other value in the range of 1%-20%.
[0078] The smaller the mass proportion of the covalent triazine framework in the coating slurry, the more uniform its dispersion in the slurry, which provides a basis for the preparation of a thinner coating layer. At the same time, it can make the covalent triazine framework more evenly distributed on the surface of the base film. After being assembled into a battery, the current distribution during the charge and discharge process can be uniform, avoiding polarization.
[0079] In some embodiments, the coating layer components are mixed with a solvent, wherein the coating layer components include a covalent triazine framework to obtain a coating slurry, including:
[0080] S1.1. The covalent triazine framework of the coating layer is dispersed in a solvent to obtain a dispersion;
[0081] S1.2. The remaining components of the coating layer are dispersed in a solvent to obtain a uniform mixture containing a binder;
[0082] S1.3. Mix the dispersion and the uniform mixture containing the binder to obtain a coating slurry.
[0083] Specifically, in this embodiment, a certain mass of a covalent triazine framework is added to a solvent and dispersed uniformly by ultrasound to obtain a first dispersion; a binder or a blend of a binder and a functional material is added to a solvent and dispersed by stirring to obtain a second dispersion; the first dispersion and the second dispersion are mixed and uniformly mixed by stirring to obtain a coating slurry.
[0084] The solvent may be selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide, or the solvent may be selected from at least one of deionized water, ethanol, propylene glycol, and glycerol.
[0085] S2. applying the coating slurry to the base film, and then removing the solvent to obtain a coated diaphragm;
[0086] Specifically, in this embodiment, the coating slurry is coated on one side or both sides of the polyolefin separator, and then dried to remove the solvent in the coating layer to obtain a coated separator.
[0087] The coating method includes any one of scraper coating, roller coating, spray coating and spot coating.
[0088] The coated diaphragm prepared by the above method has advantages in preparation and performance compared with the existing coated diaphragms. The existing coated diaphragms have increased preparation costs due to the thick coating layer, and the coating layer will cause the porosity to decrease and the lithium ion migration path to become longer. The coated diaphragm of this scheme can form a non-completely covered coating layer on the surface of the polyolefin diaphragm by adjusting the appropriate ratio of the covalent triazine framework and the binder. The coating layer thickness is less than 2 microns, which will not affect the migration of ions, and saves costs, which is conducive to industrial production.
[0089] An embodiment of the present application provides a lithium battery, which includes the coated diaphragm provided above or a coated diaphragm prepared by the method for preparing the coated diaphragm provided above.
[0090] The lithium battery can be a lithium ion battery, a lithium metal battery, etc. Among them, the lithium ion battery is assembled by a coated diaphragm, a positive electrode containing lithium iron phosphate, a graphite negative electrode and an electrolyte; the lithium metal battery is assembled by a coated diaphragm, a positive electrode containing lithium iron phosphate, a metal lithium negative electrode and an electrolyte.
[0091] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0092] Examples 1-17
[0093] A method for preparing a coated diaphragm comprises the following specific steps:
[0094] (1) adding a covalent triazine framework to a solvent and dispersing it uniformly by ultrasound to obtain a first dispersion; and adding a binder or a mixture of a binder and a functional material to an equal amount of the solvent and dissolving them by stirring to obtain a second dispersion containing the binder;
[0095] (2) mixing the first dispersion obtained in (1) and the second dispersion containing a binder uniformly by stirring to obtain a coating slurry;
[0096] (3) applying the coating slurry obtained in (2) on the surface of the base film to obtain a slurry-coated diaphragm;
[0097] (4) The slurry-coated separator obtained in (3) is dried to remove the solvent in the coating layer, thereby obtaining a coated separator.
[0098] The main parameter control of each embodiment is shown in the following table:
[0099]
[0100]
[0101] The first structure refers to:
[0102]
[0103] Comparative Example 1
[0104] The polyethylene commercial separator was purchased from Shenzhen Xingyuan Material Technology Co., Ltd., with a thickness of 19 μm and a wet-process biaxially oriented single-layer polyethylene separator.
[0105] Comparative Example 2
[0106] The polyolefin diaphragm is coated with Al2O3, wherein the polyolefin diaphragm is purchased from Shenzhen Xingyuan Material Technology Co., Ltd., has a thickness of 11 μm, and the thickness of the Al2O3 coating layer is 2 μm.
[0107] Comparative Example 3
[0108] The polyolefin diaphragm is coated with acetic acid acrylic acid copolymer (EAA), and the preparation process includes: 1% EAA by mass is dissolved in a mixed solvent of tetrahydrofuran and dioctyl phthalate (mass fraction 1:1), and then coated to obtain a polyolefin diaphragm coated with acetic acid acrylic acid copolymer (EAA), wherein the polyolefin diaphragm is purchased from Shenzhen Xingyuan Materials Technology Co., Ltd., with a thickness of 12μm, and the thickness of the acetic acid acrylic acid copolymer (EAA) coating layer is 1μm.
[0109] The coating layer of the coated diaphragm provided in each embodiment was subjected to an electron microscope scanning test. Since the results are similar, only the SEM result of the coating layer provided in Example 1 is used for illustration. Figure 1 As shown, Figure 1 This is a SEM image of the coating layer provided in Example 1 of the present application. It can be seen from the image that the covalent triazine framework coating is evenly distributed on the surface of the polyethylene diaphragm, covering the microporous part of the polyethylene diaphragm.
[0110] The separators provided in each embodiment and comparative example were assembled into lithium metal batteries, and the constant rate charge and discharge curves of the batteries at 1C were measured to obtain the initial discharge specific capacity. The constant rate charge and discharge curves of Example 1 are as follows: Figure 2 As shown, after 120 cycles, the capacity decay rate of each cycle was calculated. At the same time, the ionic conductivity curve obtained by the AC impedance spectrum was used to obtain the ionic conductivity, wherein the ionic conductivity curve of Example 1 is as shown Figure 3 As shown, in addition, an electrolyte was dripped onto the diaphragm provided in each embodiment and comparative example, and its contact angle was tested, wherein, Figure 4 and Figure 5 This is a graph showing the optical test results of the contact angle of the electrolyte of the coated diaphragm provided in Example 1 of the present application. Figure 6 and Figure 7 This is a graph showing the optical test results of the electrolyte contact angle of the diaphragm provided in Comparative Example 1 of the present application. The results are shown in the following table:
[0111]
[0112] It can be seen from the above table that the diaphragm prepared by the method provided in the embodiment of the present application has good results in the tests of initial discharge specific capacity, capacity decay rate, ionic conductivity and contact angle, and has high comprehensive performance. Through the comparison of the data of Examples 1 to 5, it can be seen that with the increase of the mass fraction of the covalent triazine framework in the coating layer, the initial discharge specific capacity and ionic conductivity of the battery both increase. It can be seen that the increase of the covalent triazine framework can increase the battery capacity and reduce the internal polarization of the battery. At the same time, with the increase of the mass fraction of the covalent triazine framework in the coating layer, the capacity decay rate and contact angle of the battery gradually decrease. It can be seen that the covalent triazine framework can increase the cycle performance of the battery and the affinity for the electrolyte, but after increasing to a certain extent, the proportion of other components such as binders is too small, which makes it difficult to form a stable coating layer. Through the comparison of Examples 6 to 10 and Example 1, it can be seen that with the decrease of the thickness of the coating layer, the ionic conductivity of the battery gradually increases, and the ionic conductivity can be maintained at 0.7mS cm when the thickness is 0.3 to 2μm. -1 The above is a preferred range. At the same time, the applicant believes that the difficulty in operating the battery when the coating layer thickness is less than 0.2 μm is due to the limitations of the current coating and test conditions. In fact, the performance should be better than that of the uncoated separator. By comparing Examples 6 to 10 with Example 1, it can be seen that as the coating amount of the coating layer decreases, the ionic conductivity of the battery gradually increases, and when the coating amount of the coating layer is 0.014-0.09 mg cm -2 The ionic conductivity can be maintained at 0.7 mS cm -1 The above is a preferred range; through comparison of the data from Example 11 to Example 15, it can be obtained that with the increase of the mass fraction of the covalent triazine framework in the coating slurry, the battery capacity, internal polarization and cycle performance of the battery all show a trend of first increasing and then decreasing, and at the same time, the affinity for the electrolyte gradually increases. It can be seen that controlling the mass fraction of the covalent triazine framework in the coating slurry to 1% to 20% is a preferred range, which can make the overall performance of the battery better.
[0113] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A coated diaphragm, characterized in that: The coated membrane comprises: a base film and a coating layer; the coating layer is attached to at least a portion of the base film, and the coating layer comprises a covalent triazine framework.
2. The coated diaphragm according to claim 1, characterized in that The covalent triazine framework comprises a plurality of interconnected microporous units, and the structural formula of the microporous unit is: wherein R comprises at least one of a benzene ring, biphenyl, pyridine, naphthalene and anthracene; It includes at least one of a triazine structure and a triphenylamine structure, and at least one It is a triazine structure.
3. The coated diaphragm according to claim 2, characterized in that: The covalent triazine framework comprises: At least one of .
4. The coated diaphragm according to claim 1, characterized in that The mass of the covalent triazine framework is 50%-90% of the mass of the coating layer; or The mass of the covalent triazine framework is 70%-90% of the mass of the coating layer.
5. The coated diaphragm according to claim 1, characterized in that The coating layer has an attachment amount of 0.01-0.1 mg / cm 2 ;or The coating layer has an attachment amount of 0.01-0.05 mg / cm 2 .
6. The coated diaphragm according to claim 1, characterized in that The coating layer has a thickness of 0.1-2 μm; or The coating layer has a thickness of 0.21-2 μm; or The coating layer has a thickness of 0.3-1 μm; or The coating layer has a thickness of 0.3-0.8 μm.
7. The coated diaphragm according to claim 1, characterized in that The size of the covalent triazine framework is 0.1-2 μm; or The size of the covalent triazine framework is 0.1-1.0 μm; or The size of the covalent triazine framework is 0.2-0.8 μm.
8. The coated diaphragm according to claim 1, characterized in that The coating layer is attached to at least a portion of one side of the base film, or the coating layer is attached to at least a portion of both sides of the base film.
9. The coated diaphragm according to claim 1, characterized in that The coating layer also includes a binder, and the binder includes an oily binder or an aqueous binder; optionally, the oily binder includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer and polyimide, and the aqueous binder includes at least one of polyacrylic acid binder, polyurethane binder, polyacrylonitrile binder, polyacrylate binder, carboxymethyl cellulose lithium binder, carboxylated chitosan binder, styrene-butadiene emulsion and polytetrafluoroethylene emulsion; and / or The coating layer also includes a functional material, wherein the functional material includes at least one of aluminum oxide, silicon nitride, titanium nitride, aluminum nitride, zirconium diboride, zirconium nitride, molybdenum nitride, boron nitride, carbon nitride, molybdenum disulfide, molybdenum antimonide, tungsten disulfide, calcium sulfide and titanium selenide; and / or The base film is a polyolefin membrane; optionally, the polyolefin membrane is a polypropylene membrane, a polyethylene membrane, or a polypropylene / polyethylene / polypropylene three-layer composite membrane.
10. A method for preparing a coated diaphragm, characterized in that: The method comprises: Mixing the coating layer components with a solvent, wherein the coating layer components include a covalent triazine framework to obtain a coating slurry; The coating slurry is applied to a base film, and then the solvent is removed to obtain a coated separator.
11. The method for preparing a coated diaphragm according to claim 10, characterized in that: The mass proportion of the covalent triazine framework in the coating slurry is 1%-20%; or The mass proportion of the covalent triazine framework in the coating slurry is 1%-10%; or The mass proportion of the covalent triazine framework in the coating slurry is 1%-5%; or The mass proportion of the covalent triazine framework in the coating slurry is 3%-5%.
12. The method for preparing a coated diaphragm according to claim 10, characterized in that: The coating layer components are mixed with a solvent, wherein the coating layer components include a covalent triazine framework to obtain a coating slurry, including: Dispersing the covalent triazine framework in the coating layer in a solvent to obtain a first dispersion; dispersing the remaining components of the coating layer in a solvent, wherein the remaining components include a binder, to obtain a second dispersion; The first dispersion liquid and the second dispersion liquid are mixed to obtain a coating slurry.
13. A lithium battery, characterized in that: The lithium battery comprises the coated diaphragm according to any one of claims 1 to 9 or the coated diaphragm prepared by the method for preparing the coated diaphragm according to any one of claims 10 to 12.
Citation Information
Cited By
Lithium ion battery diaphragm as well as preparation method and application thereof
CN121642435A
Battery diaphragm and lithium ion battery
CN121642436A